GAMBARAN SUPERVISI, IKLIM KERJA SERTA KEPUASAN KERJA KARYAWAN PT. TRIBUANA REKAYASA BANDUNG - Robissalami, Devi; Sumiyati, Sumiyati; Tarmedi, Eded (Journal of Business Management Education (JBME), 2018)
Purpose - The purpose of this study is to determine the effect of supervision and working climate on employee job satisfactionDesign / methodology / approach - This research was conducted in less than 1 year period, the research design is cross-sectional design. The method used is exolanatory survey, and population 67 employees. The analysis technique used is descriptive, the questionnaire is used as a research instrument to collect data from respondents.Findings - based on the results of the study using multiple linear regression analysis, the result that there is a positive influence of supervision and work climate on employee job satisfaction.Originality / value - this study provides a basis for find out the impact of supervision and working climate on employee job satisfaction. The difference of this study with previous research is on the objects, variables, theories and the references.